Effectiveness of structured multidisciplinary rounding in acute care units on length of stay and satisfaction of patients and staff: a quantitative systematic review. (July 2016) - Mercedes, Angela; Fairman, Precillia; Hogan, Lisa; Thomas, Rexi; Slyer, Jason T.
EXECUTIVE SUMMARY: Background: Consistent, concise and timely communication between a multidisciplinary team of healthcare providers, patients and families is necessary for the delivery of quality care. Structured multidisciplinary rounding (MDR) using a structured communication tool may positively impact length of stay (LOS) and satisfaction of patients and staff by improving communication, coordination and collaboration among the healthcare team. Objectives: To evaluate the effectiveness of structured MDR using a structured communication tool in acute care units on LOS and satisfaction of patients and staff. Inclusion criteria Types of participants : Adult patients admitted to acute care units and healthcare providers who provide direct care for adult patients hospitalized in in-patient acute care units. Type of intervention : The implementation of structured MDR utilizing a structured communication tool to enhance and/or guide communication. Types of studies : Quasi-experimental studies and descriptive studies. Outcomes : Length of stay, patient satisfaction and staff satisfaction. Search strategy: The comprehensive search strategy aimed to find relevant published and unpublished quantitative English language studies from the inception of each database searched through June 30, 2015. Databases searched include Cumulative Index to Nursing and Allied Health Literature, PubMed, Excerpta Medica Database, Health Source, Cochrane Central Register of Controlled Trials and Scopus. A search of gray literature was also performed. Methodological quality: All reviewers independently evaluated the included studies for methodological quality using critical appraisal tools from the Joanna Briggs Institute (JBI). Data extraction: Data related to the methods, participants, interventions and findings were extracted using a standardized data extraction tool from the JBI. Data synthesis: Due to clinical and methodological heterogeneity in the interventions and outcome measures of the included studies, statistical meta-analysis was not possible. Results are presented in narrative form. Results: Eight studies were included, three quasi-experimental studies and five descriptive studies of quality improvement projects. In the three quasi-experimental studies, one had a statistically significant decrease ( p = 0.01), one no change ( p = 0.1) and one had an increase ( p = 0.03) in LOS; in the two descriptive studies, one had a statistically significant decrease ( p = 0.02) and the other reported a trend toward reduced LOS. Two studies evaluated patient satisfaction, one showed no change ( p = 0.76) and one showed a trend toward increased patient satisfaction at 12 months. Six studies demonstrated an improvement in staff satisfaction ( p < 0.05) after implementation of structured MDR. Conclusion: The evidence suggests that MDR utilizing a structured communication tool may have contributed to an improvement in staff satisfaction. There was inconclusive evidence to support the use of structured MDR to improve LOS or patient satisfaction. The use of a structured communication tool during MDR is one means to facilitate communication and collaboration, thus improving satisfaction among the multidisciplinary team. More rigorous research using higher level study designs on larger samples of diverse patient populations is needed to further evaluate the effectiveness of structured MDR on patient care outcomes and satisfaction of patients and providers.